A Proximate Remove Queering Intimacy and Loss in The Tale of Genji (Edition 1) - Jackson, Reginald (University of California Press, 2021)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. How might queer theory transform our interpretations of medieval Japanese literature and how might this literature reorient the assumptions, priorities, and critical practices of queer theory? Through a close reading of The Tale of Genji, an eleventh-century text that depicts the lifestyles of aristocrats during the Heian period, A Proximate Remove explores this question by mapping the destabilizing aesthetic, affective, and phenomenological dimensions of experiencing intimacy and loss. The spatiotemporal fissures Reginald Jackson calls "proximate removes" suspend belief in prevailing structures. Beyond issues of sexuality, Genji queers in its reluctance to romanticize or reproduce a flawed social order. An understanding of this hesitation enhances how we engage with premodern texts and how we question contemporary disciplinary stances.